Reputation:
I am trying to see the equivalence of the XOR expression but I cannot. I am trying to express a XOR with only NANDs
A^B
=AB'+A'B
=(A+B)(AB)' <= This the transformation I don't understand.
=((A(AB)')'(B(AB)')')'
Thanks a lot for the help :)
Upvotes: 1
Views: 1164
Reputation: 1352
Let's go backwards with more steps
(A+B)(AB)'
<=>A(AB)' + B(AB)'
(distributivity)
<=>A(A'+B') + B(A'+B')
(demorgan on (AB)'
)
<=>AA' + AB' + BA' + BB'
(distributivity)
Since AA'
and BB'
evaluate to false (i.e. T AND F or F AND T result in False), they can be removed from the chained or-condition leaving (False OR X <=> X)
AB' + A'B
So back to the original . . .
1) they start with the AB' + A'B
2) added the terms AA'
and BB'
giving AA' + AB' + BA' + BB'
3) factored out (A'+B')
leaving A(A' + B') + B(A' + B')
4) Rearranged to (A+B)(A'+B')
4) Finally demogran law to result in (A+B)(AB)'
Upvotes: 3